Symphony of monsters : a novel - Levy, Marc, 1961- (HarperVia, an imprint of HarperCollins Publishers, 2026)
"Set against the backdrop of the war in Ukraine, international bestselling author Marc Levy's new novel is a page-turning thriller full of courage, resilience, and love"-- Provided by publisher.